A chaos study of tumor and effector cells in fractional tumor-immune model for cancer treatment. (December 2020) - Kumar, Sunil; Kumar, Ajay; Samet, Bessem; Gómez-Aguilar, J.F.; Osman, M.S.
Highlights: A comparative and chaotic study of tumor and effector cells through fractional tumor-immune dynamical model was investigated. Performance was done using the strategy of Adams-Bashforth-Moulton and Toufik-Atangana methods. The existence and uniqueness of the given tumor-immune model of arbitrary order are analyzed. Abstract: A tumor is most dangerous disease of medical science which is a mass or lumps of tissue that's formed by an accumulation of abnormal cells. A famous fractional tumor-immune model is interpreting the dynamics of tumor and effector cells. In this work, we provide a comparative and chaotic study of tumor and effector cells through fractional tumor-immune dynamical model. A new arbitrary operator based on the Mittag-Leffler law is assumed for this study. Again, we examine the interactions among distinct tumor cell inhabitants and immune structure through a model of real world problem of medical science. We First investigate the dynamical effect of the activation of the effector immune and tumor cells by using Adams-Bashforth-Moulton and Toufik-Atangana methods. Furthermore, this paper analyses the existence and uniqueness of given tumor-immune model of arbitrary order. Further, we have examined the dynamical behaviors of the fractional tumor-immunne model and obtained results are compared with exiting results by other methods. Numerical simulations are executed by Adams-Bashforth-Moulton and Toufik-Atangana methods using popular Atangana-Baleanu fractional derivative. Our obtained results will be useful for biologists to the treatment of cancer disease.